More Than a Roof? An Evaluation of Post-Prison Housing Provision in Aotearoa New Zealand - Mills, Alice; Lindsay, Cinnamon; Gordon, Grace; Groot, Shiloh; Milne, Barry (New Zealand Sociology, 2021)
Many people in prisons in Aotearoa New Zealand will have nowhere to go on release and few will settle into long-term accommodation. Post-release stable housing has been linked with reduced rates of recidivism, but up until recently, has received little official attention in Aotearoa New Zealand. This article provides a critical evaluation of the provision of post-prison housing in Aotearoa New Zealand. It examines the substantial barriers to finding stable accommodation faced by those leaving prison and argues that current post-prison housing provision is inadequate, inflexible and precarious, and largely unsuitable for MÄori. It concludes that substantial reforms to post-prison housing are needed, including the introduction of MÄori-led, whÄnau-centred initiatives, to break the cycle of homelessness and recidivism.